Exploring the Factor Structure of the NIH Toolbox Cognition Battery in a Large Sample of 8-Year-Old Children in Aotearoa New Zealand. (11th September 2021) - Neumann, Denise; Peterson, Elizabeth R.; Underwood, Lisa; Morton, Susan M.B.; Waldie, Karen E.
Abstract: Objective: The objective of this study was to derive a factor structure of the measures of the National Institutes of Health (NIH) Toolbox Cognition Battery (CB) that is representative of cognitive abilities in a large ethnically diverse cohort of 8-year-old children in Aotearoa New Zealand. Methods: Our sample comprised of 4298 8-year-old children from the Growing Up in New Zealand study. We conducted exploratory and confirmatory factor analysis for the NIH Toolbox CB measures to discover the best-fitting factor structure in our sample. Measurement invariance of the identified model was tested across child's gender, socio-economic status (SES), and ethnicity. Results: A three-dimensional factor structure was identified, with one factor of Crystallised Cognition (Reading and Vocabulary), and two distinguished factors of fluid cognition: Fluid Cognition I (Attention/Inhibitory Control, Processing Speed, and Cognitive Flexibility) and Fluid Cognition II (Working Memory, Episodic Memory). The results demonstrate excellent model fit, but reliability of the factors was low. Measurement invariance was confirmed for child's gender. We found configural, but neither metric nor scalar, invariance across SES and the four major ethnic groups: European, Māori, Pacific Peoples, and Asian. Conclusion: Our findings show that, at the age of 8 years, fluid abilities are more strongly associated with one another than with crystallised abilities and that fluid abilities need to be further differentiated. This dimensional structure allows for comparisons across child's gender, but evaluations across SES and ethnicity within the Aotearoa New Zealand context must be conducted with caution. We recommend using raw scores of the individual NIH Toolbox CB measures in future research.